Olmsted syndrome in three siblings - Mrinal Gupta (Wolters Kluwer Medknow Publications, 2017)
Olmsted syndrome (OS) is a rare congenital, sharply circumscribed transgredient palmoplantar keratoderma, first described by Olmsted in 1927, characterized by clinical features such as symmetrical involvement of keratoderma of the palms and soles and the symmetrical hyperkeratotic plaques around the body orifices. Other clinical findings include flexion deformities of the fingers, localized alopecia, leukokeratosis of the tongue, short stature, and laxity of the large joints. It starts in the neonatal period or in childhood. The disease has a slow but progressive and extremely disabling course. Treatment of OS is often based on topical therapy with retinoic acid, corticosteroid, emollients, and keratolytics. We present a case of OS in three siblings, two males and a female, born to nonconsanguineous parents with no family history. They were treated with topical corticosteroids and emollients and showed mild improvement in symptoms.